Wear-resistant nanofiber reinforced protective graphene fiber as well as preparation method and application thereof

Through electrospinning technology, nanofiber films are formed on graphene fibers and heat-pressing rollers are processed, which solves the problem of insufficient wear resistance and mechanical properties of graphene fibers, and significantly improves its electrical conductivity, thermal conductivity and wear resistance.

CN119900120AActive Publication Date: 2025-04-29DONGHUA UNIV

Patent Information

Application Number
CN202510391924.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-31
Publication Date
2025-04-29
Estimated Expiration
2045-03-31

AI Technical Summary

Technical Problem

Due to its brittleness and roughness of the surface, graphene fibers have insufficient wear resistance and are difficult to braid and mold, and the gaps between the fibers affect electrical and thermal conductivity.

Method used

The nanofiber film is formed on the graphene fibers by electrospinning technology and heat-pressing roller treatment is carried out to enhance the wear resistance and mechanical properties of the fibers while optimizing the conductivity and thermal conductivity.

Benefits of technology

The tensile strength, elastic modulus, toughness, electrical conductivity and thermal conductivity of graphene fibers are significantly improved, and the specific wear rate is reduced, enhancing the overall performance of the fibers.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119900120A_ABST
    Figure CN119900120A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of functional composite fibers, and discloses a wear-resistant nanofiber-reinforced protective graphene fiber and a preparation method and application thereof.The wear-resistant nanofiber-reinforced protective graphene fiber comprises a graphene fiber tow and nanofibers, the nanofibers coat the graphene fiber tow in a three-dimensional porous network mode, and the nanofibers coat the graphene fiber tow in a three-dimensional porous network mode. Forming a stress buffer layer; wear-resistant particles are uniformly loaded in the three-dimensional porous network; the preparation method comprises the following steps: fixing the graphene fibers subjected to surface pretreatment on an electrostatic spinning nano-yarn machine, forming a nano-fiber membrane by utilizing electrostatic spinning, uniformly wrapping the graphene fibers subjected to surface pretreatment with the nano-fiber membrane, then rolling into a shaft, and then carrying out hot-pressing roller treatment on the rolled fiber bundle, so as to obtain the graphene nano-yarn. The wear-resistant nanofiber reinforced protective graphene fiber is prepared; the graphene fiber is used for weaving to obtain the graphene fiber fabric. The fiber prepared by the invention and a fabric woven by using the fiber have excellent mechanical properties, wear resistance, electric conductivity and heat conductivity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of functional composite fibers and relates to a wear-resistant nanofiber reinforced protective graphene fiber and a preparation method and application thereof. Background Art

[0002] In the field of preparing functional composite fiber materials, graphene fiber is gradually becoming the focus of research due to its unique electronic, thermal and mechanical properties. This two-dimensional structural material composed of a single layer of carbon atoms has a very high specific surface area, excellent electrical and thermal conductivity, high strength and high ductility. These characteristics give graphene-based fibers the potential for wide application in high-tech fields such as composite materials, sensors, flexible electronics, energy storage and conversion, etc.

[0003] However, although graphene fibers have attracted widespread attention due to their excellent electrical conductivity and high specific strength, they still face a series of challenges in the process of transforming them into practical engineering materials. First, although graphene fibers have high mechanical strength and good electrical conductivity, they are brittle and easily affected by friction or wear. Since the surface of graphene fibers is rough and the pores are not completely filled, this leads to insufficient wear resistance, making it difficult to continuously weave the fibers into shape.

[0004] The root of the above problems is that graphene sheets are mainly bonded to each other through π-π stacking and van der Waals forces. This non-covalent force is relatively weak and cannot withstand large mechanical stress. Therefore, under the action of tensile, bending or shear loads, the non-covalent bonds between the internal layers of graphene fibers are easily separated, increasing the risk of structural fracture. During the fiber making and weaving process, the sheets on the surface of the graphene fiber bundles are easily peeled off due to friction or extrusion stress, forming loose flying filaments or even breaking, which seriously affects the consistency and overall mechanical properties of the fiber bundles, making the fiber bundles difficult to weave.

[0005] In addition, there are large gaps between the graphene fiber strands in the woven graphene fiber bundle, and even after twisting, it is difficult to completely remove these gaps. These gaps not only affect the transmission of electrons and phonons in the vertical direction, but also reduce the thermal conductivity and electrical conductivity of the material, which in turn leads to a decrease in mechanical properties during application.

[0006] In order to improve this problem, the sizing process commonly used in the prior art can make the fiber bundles tightly bundled by coating them, but due to the rough surface of the graphene fiber monofilaments, there are still gaps between the monofilaments after bundling. These gaps cannot be completely filled after sizing and coating, resulting in the wear resistance of the surface of the tow being difficult to meet the weaving requirements. Therefore, it is necessary to explore other surface treatment technologies to enhance the wear resistance, mechanical properties (including strength, flexibility, modulus), and electrical and thermal conductivity of the fiber bundles.

[0007] At present, although there are few protective treatment technologies for graphene fibers, researchers are exploring ways to improve the surface properties of fiber bundles by referring to the sizing technology of fibers similar to graphene fibers (such as carbon fibers, basalt fibers, glass fibers, etc.). By introducing new treatment processes or reinforcing agents on the fiber surface, the processing properties of the fibers can be improved, the interfacial bonding between fiber bundles can be increased, and the overall mechanical, electrical and thermal conductivity of the fibers can be improved.

[0008] The patent with the authorization announcement number CN105254920B discloses a method for preparing graphene paper prepreg, which is to immerse the graphene paper-like material in an epoxy resin solution to obtain a composite material, and the prepreg retains the excellent conductive properties of graphene after curing. However, the mismatch between the interface of graphene and epoxy resin still leads to interlayer separation of the composite material during high stress deformation.

[0009] The patent application with application publication number CN118996562A discloses an anodic oxidation method for high-strength medium-modulus polyacrylonitrile-based carbon fiber and carbon fiber. The method is to subject the carbonized high-strength medium-modulus polyacrylonitrile-based carbon fiber to a primary anodic oxidation treatment in an inorganic electrolyte, and then to a secondary anodic oxidation treatment in an organic electrolyte. In this way, the strength of the carbon fiber can be significantly reduced while improving the interface performance of the high-strength medium-modulus polyacrylonitrile-based carbon fiber. However, anodic oxidation mainly improves the interface performance and has limited contribution to the surface wear resistance. The surface layer generated after oxidation is relatively fragile and easily wears or peels off under high friction or impact conditions. In particular, in the secondary anodic oxidation (organic electrolyte environment), improper control may further damage the mechanical properties of the fiber.

[0010] Reference 1 (Construction of cellulose nanofiber / carbon nanotube synergistic network on carbon fiber surface to enhance mechanical properties and thermal conductivity of composites[J]. Composites Science and Technology, 2024, 3(22):110454) uses a combination of polydopamine (PDA), cellulose nanofibers (CNF), polyvinyl alcohol (PVA) and amino carbon nanotubes (CNT) to form a synergistic network on the surface of carbon fiber (CF) through hydrogen and covalent bonds. This strategy significantly enhances the flexural strength, flexural modulus, interlaminar shear strength (ILSS), tensile strength and interfacial shear strength (IFSS) of the resulting composite material. However, this structure has limited improvement in wear resistance because its surface coating is soft and the wear resistance of PVA and CNF is weak, making it difficult to effectively resist long-term friction and mechanical damage.

[0011] Reference 2 (Growing Carbon Nanotubes In Situ Surrounding Carbon Fiber Surface via Chemical Vapor Deposition to Reinforce Flexural Strength of Carbon Fiber Composites[J]. Polymers 2023, 15(10), 2309) describes the in-situ preparation of vertically aligned carbon nanotubes (VACNTs) on a catalyst-treated CF surface by chemical vapor deposition (CVD), interweaving into a three-dimensional fiber network and completely surrounding the CF to form an integrated structure. It has great potential in the manufacture of high-strength CFRP composites for aerospace applications. However, the main function of VACNT is to enhance the interface bonding performance and overall mechanical properties, while carbon nanotubes themselves are relatively fragile and have weak wear resistance, especially in long-term high-friction environments, where they may easily fall off or be damaged; and the vertically arranged structure may deteriorate in overall performance due to local fracture when worn.

[0012] Therefore, it is of great significance to study a wear-resistant nanofiber reinforced protective graphene fiber and its preparation method and application to solve the above problems. Summary of the invention

[0013] The purpose of the present invention is to solve the problems existing in the prior art and to provide a wear-resistant nanofiber reinforced protective graphene fiber and a preparation method and application thereof.

[0014] To achieve the above object, the technical solution adopted by the present invention is as follows:

[0015] The preparation method of wear-resistant nanofiber reinforced protective graphene fiber comprises the following steps: fixing the surface pretreated graphene fiber on an electrostatic spinning nano yarn machine (the electrostatic spinning nano yarn machine is a prior art, and the surface pretreated graphene fiber is fixed in the following manner: manually pulling out the end of the graphene fiber bundle on the spinning reel from the conical yarn guide on the left, adjusting the tension of the pulled fiber bundle by a control device, and then leading the bundle to the guide hole on the right, fixing it on the clamp of the wire collection device, and controlling the winding speed of the bundle by a motor drive system), forming a nanofiber membrane by electrostatic spinning and uniformly wrapping it on the surface pretreated graphene fiber, and then winding it into a shaft, and then subjecting the wound fiber bundle to a hot pressing roller treatment to obtain the wear-resistant nanofiber reinforced protective graphene fiber;

[0016] The rolled fiber bundle is subjected to hot pressing roller treatment, which can remove the defects on the surface of the nanofiber membrane, deform and fuse the nanofiber membrane on the surface, improve the surface smoothness and reduce the surface unevenness; at the same time, it can reduce the gaps between the nanofibers, promote the diffusion and penetration of the polymer chain on the graphene surface, make the interface between the nanofiber and the graphene more stable, improve the density and strength of the fiber bundle, and evenly coat the fiber bundle, which is helpful to improve the density and strength of the wear-resistant nanofiber reinforced protection graphene fiber, and the heat can increase the fluidity of the polymer chain, so that it can better fill the microscopic concave-convex structure of the graphene and increase the actual contact area; at the same time, the heat treatment can relax the internal stress formed in the spinning process, reduce the probability of microscopic cracks and interface peeling inside the material, and can also help remove the solvent that may not be completely volatilized during the formation of the polymer nanofiber membrane, which helps to reduce the fragile interface between the graphene and the nanofiber membrane caused by the solvent residue;

[0017] The surface pretreatment adopts the method of plasma irradiation treatment. The active oxygen species (O + , O 2 + , O 3 ) reacts with carbon atoms on the graphene surface to generate oxygen-containing functional groups such as carboxyl (-COOH), hydroxyl (-OH), and epoxy (COC). Plasma irradiation treatment etches a small amount of active sites on the inert graphene fiber surface, making it easier to interact with interface materials and anchor interface load materials.

[0018] The spinning solution used in electrospinning is obtained by adding wear-resistant particles to a polymer material solution; the wear-resistant particles are silicon dioxide (SiO 2 )、Alumina(Al 2 O 3 ), zirconium oxide (ZrO), boron nitride nanotubes (BNNTs), graphene powder (GPs) and titanium carbide MXene (Ti 2 C 3 Tx), the polymer material is polyurethane (PU), polyetherimide (PEI), poly(m-phenylene isophthalamide) (PMIA), poly(p-phenylene terephthalamide) (PPTA), polybenzimidazole (PBI), polyimide (PI), poly(p-phenylene benzobisoxazole) fiber (PBO) or poly-2,5-dihydroxy-1,4-phenylene pyridinium diimidazole (PIPD).

[0019] As the preferred technical solution:

[0020] In the preparation method of wear-resistant nanofiber reinforced protective graphene fiber as described above, the plasma irradiation treatment adopts an oxygen atmosphere, the pressure in the reaction chamber is 10~100Pa, the oxygen flow rate is 20~100sccm, the irradiation power is 50~200W, and the treatment time is 30~300s.

[0021] In the preparation method of wear-resistant nanofiber reinforced protective graphene fiber as described above, the mass ratio of wear-resistant particles to polymer material is 1:10-50, and the concentration of polymer material solution is 1-20wt%.

[0022] The preparation method of the wear-resistant nanofiber reinforced protective graphene fiber as described above, the spinning process parameters are: voltage 15~39kV, the distance between the needle and the collector (i.e., the electrospinning nano yarn machine) is 5~8cm, the propulsion pump rate is 0.5~2mL / h, the fiber reel winding rate is 0.1~2cm / min, the drying temperature is 50~80℃, and the spinning time is 0.5~2h.

[0023] According to the preparation method of wear-resistant nanofiber reinforced protective graphene fiber as described above, the average fiber diameter in the nanofiber membrane is 50-1000 nm, and the thickness of the nanofiber membrane is 3-100 μm.

[0024] According to the preparation method of wear-resistant nanofiber reinforced protective graphene fiber as described above, the process parameters of hot pressing roller treatment are: roller temperature 160~400℃, the roller temperature is set according to the characteristics of the treated material, roller pressure 5~20MPa, the roller pressure is set according to the type of fiber and the required densification effect, roller speed 0.5~2m / min, roller gap 80~200μm, the roller gap refers to the minimum spacing between two parallel hot pressing rollers (usually in microns), which can be adjusted according to the thickness of the composite fiber bundle. During the continuous fiber processing process, when the graphene fiber containing the nanofiber coating passes through the gap, it is densified and interface strengthened by the action of hot pressing. After the hot rolling is completed, the roller temperature is gradually reduced, and the pressure is appropriately reduced to avoid deformation or damage of the fiber bundle after hot pressing due to a sudden drop in temperature or excessive pressure.

[0025] The present invention also provides wear-resistant nanofiber reinforced protective graphene fibers prepared by the preparation method described in any one of the above, including graphene fiber bundles and nanofibers, wherein the nanofibers are coated with the graphene fiber bundles in the form of a three-dimensional porous network to form a stress buffer layer, which absorbs friction energy through elastic deformation and reduces the surface specific wear rate; the wear-resistant particles are uniformly loaded inside the three-dimensional porous network to form a transfer film at the friction interface to dynamically reduce the friction coefficient. Through the multi-level structural design and interface optimization of the nanofiber reinforcement layer, a breakthrough improvement in the wear resistance of the graphene fiber bundle matrix is ​​achieved, while retaining its intrinsic advantages of high conductivity and high strength.

[0026] As the preferred technical solution:

[0027] As described above, compared with the graphene fibers without any treatment, the wear-resistant nanofiber reinforced protective graphene fibers have a tensile strength increased by 30~65%, a tensile elastic modulus increased by 25~60%, a toughness increased by 10~40%, an electrical conductivity increased by 8~40%, a thermal conductivity increased by 10~50%, a bending strength increased by 35~65%, a bending modulus increased by 40~75%, a bending curvature increased by 10~25%, and a specific wear rate reduced by 50~80%.

[0028] The present invention provides an application of the wear-resistant nanofiber reinforced protective graphene fiber as described in any one of the above items, which is applied to weaving and preparing graphene fiber fabrics.

[0029] As the preferred technical solution:

[0030] The wear-resistant nanofiber reinforced protective graphene fiber application as described above is knitted, two-dimensional weaving, or three-dimensional weaving.

[0031] As described above, the application of wear-resistant nanofiber reinforced protection graphene fiber, compared with the control sample, the wear life of the graphene fiber fabric is increased by 150~240%, the tensile strength is increased by 30~55%, the bending fatigue life is increased by 80~180%, the electrical conductivity is increased by 5~20%, and the thermal conductivity is increased by 10~50%;

[0032] The preparation of the control sample is basically the same as the graphene fiber fabric, the only difference is that the fiber used for weaving is the graphene fiber after surface pretreatment, rather than the wear-resistant nanofiber reinforced protective graphene fiber.

[0033] After the wear-resistant nanofiber coating treatment, the graphene fiber tow has a relatively uniform surface structure and significantly improved wear resistance and mechanical properties, so it is suitable for weaving process. The wear-resistant nanofiber reinforced protection graphene fiber can provide excellent structural stability, enhanced mechanical strength and good flexibility during the weaving process, so as to adapt to complex weaving needs and can be woven into cloth through knitting, two-dimensional weaving or three-dimensional weaving technology. The prepared graphene fiber fabric has excellent wear resistance and mechanical properties, and is suitable for military clothing, bulletproof armor, and equipment for environments such as mechanical friction or chemical erosion.

[0034] Further applications of such composite fibers can also be extended to the electronics and energy fields. In the electronics industry, fabrics based on composite graphene fibers can be used as core materials for a new generation of flexible electronic devices, such as wearable electronics, flexible touch screens, and smart textiles, due to their excellent electrical / thermal conductivity and wear resistance. In the energy field, these fabrics can be used as supercapacitor electrodes or conductive backplanes for solar cells. High electrical conductivity and mechanical stability help improve the performance of energy storage and conversion devices. In addition, graphene fibers coated with three-dimensional nanofiber structures have specific surface area and pore characteristics, and are expected to play an important role in catalysis, filtration, and biomedical applications (such as artificial blood vessels and tissue engineering scaffolds). In the field of environmental science, conductive composite fiber materials will also have application potential because they can be used to efficiently filter particulate matter and harmful chemicals in the air.

[0035] Principle of the invention:

[0036] The structure of the silk cocoon is an optimized sample in nature. It is strong and flexible, and can effectively protect the pupa, and its outer silk fiber also shows excellent mechanical properties in many applications. In the present invention, we achieve the densification of nanofibers and the excellent mechanical properties and electrical and thermal conductivity of fiber bundles by continuously coating fiber bundles with wear-resistant nanofibers and performing hot rolling. The fiber structure coated with nanofibers has a "strong outer layer-high performance inner layer" structure similar to that of silk cocoons. The nanofiber coating layer loaded with wear-resistant particles provides mechanical reinforcement and wear-resistant protection, and the core layer retains the high electrical and thermal conductivity of graphene fibers. Similar to the outer silk fiber structure of the silk cocoon, the nanofiber loaded with wear-resistant particles presents a high degree of uniformity and toughness, can resist external wear, provide enhanced protection for the fiber, make its surface more solid, and do not affect the performance of the internal fiber. The multi-level fiber structure formed can be suitable for mechanical high-speed weaving, and has excellent wear resistance, mechanical properties and electrical and thermal conductivity after being woven into cloth, and is suitable for high value-added fields such as military protection, aerospace and intelligent textiles.

[0037] The principle of the present invention to enhance and protect graphene fibers through the wear-resistant nanofiber layer and improve mechanical properties, electrical conductivity, thermal conductivity, and wear resistance is as follows:

[0038] (1) Mechanical performance enhancement mechanism

[0039] There are a large number of wrinkles and grooves on the surface of graphene fiber monofilaments, which serve as mechanical anchoring points and can produce a "pinning effect" with the nanofiber coating. In addition, after plasma treatment, oxygen-containing functional groups (-COOH, -OH) are generated on the surface of the graphene fiber, which form hydrogen bonds and covalent bonds with polar groups (such as amino groups and amide groups) of nanofibers such as polyimide (PI) and poly(p-phenylene terephthalamide) (PPTA), thereby significantly improving the tensile strength.

[0040] Based on the nanofiber bridging effect, the nanofibers form a high-density interpenetrating network on the graphene surface (network density>10 9 / m², network density refers to the interweaving density of fibers in the nanofiber network, that is, the number of fiber interweaving points per unit area. The high-resolution image of the nanofiber membrane is obtained by scanning electron microscopy (SEM). After the image is processed by image analysis software, the number of fiber interweaving points is extracted and their density is measured to obtain the network density), and the external load is dispersed through mechanical interlocking. For example, when the fiber is stretched, the nanofiber network disperses the local stress to a larger range by bridging the two sides of the crack, inhibiting the crack propagation on the graphene fiber and greatly improving the tensile strength.

[0041] In addition, the flexible nanofiber membrane wraps the high modulus graphene fiber to form a "rigid and flexible" structure with a modulus gradient. The flexible layer is used to absorb impact energy (such as crack extension energy), while the rigid layer bears the main load. The soft and hard layers work together to improve the toughness of the composite material (toughness is increased by 2 to 3 times).

[0042] (2) Electrical / thermal conductivity optimization mechanism

[0043] After the nanofiber membrane is wrapped with graphene fibers, the graphene fibers are closely arranged through hot rolling, which significantly increases the contact area between fibers (the contact point density increases by 50-100%). At the same time, the close contact reduces the air gaps and interface defects between graphene fibers, and the transition barrier of electrons between fibers is reduced, forming a low-resistance conductive path. In addition, after densification, the van der Waals interaction between graphene fibers is enhanced, forming a continuous conductive network throughout the composite material, and the conductivity is increased to 10-40%.

[0044] (3) Wear resistance optimization mechanism

[0045] First of all, the protective effect of the nanofiber membrane. A layer of wear-resistant nanofiber is coated on the surface of the graphene fiber, and the nanofiber is densified by hot rolling technology. This layer of nanofiber coating has good hardness and anti-friction properties, which effectively reduces the friction contact between the fiber surface and external objects and improves the wear resistance of the fabric. The dense structure of the coating fills the gaps between the fibers, further improves the stability of the fiber bundle, and reduces the surface damage caused by friction; at the same time, the high-density interwoven nanofibers formed by electrospinning technology enhance the mutual connection between the graphene fibers, making the surface of the fiber bundle more solid, reducing the friction between single fibers, and reducing the probability of damage during friction; the wear-resistant particles distributed on the surface of the nanofiber have good wear resistance, which can further strengthen the fiber surface and significantly enhance its resistance to external wear.

[0046] Beneficial effects:

[0047] (1) The present invention achieves the densification of nanofibers and the excellent mechanical properties and electrical and thermal conductivity of fiber bundles by continuously coating fiber bundles with wear-resistant nanofibers and performing hot rolling. At the same time, the fiber structure coated with nanofibers has a "strong outer layer-high performance inner layer" structure similar to that of a silkworm cocoon. The nanofiber coating layer loaded with wear-resistant particles provides mechanical reinforcement and wear-resistant protection, and the core layer retains the high electrical and thermal conductivity characteristics of graphene fibers.

[0048] (2) The present invention significantly improves the tensile strength by creating a "pinning effect" between the wrinkles and grooves on the surface of the graphene fiber monofilament and the nanofiber coating layer, and then using the oxygen-containing functional groups generated on the surface of the graphene fiber to form hydrogen bonds and covalent bonds with the polar groups of the nanofiber.

[0049] (3) The present invention arranges graphene fibers closely through hot rolling, significantly increases the contact area between fibers, reduces the air gaps and interface defects between graphene fibers, reduces the transition barrier of electrons between fibers, forms a low-resistance conductive path, and thus improves the electrical conductivity.

[0050] (4) The present invention coats the graphene fiber surface with a layer of wear-resistant nanofibers and performs a hot rolling treatment, so that the nanofiber coating layer has good hardness and anti-friction performance, effectively reducing the friction contact between the fiber surface and external objects, and improving the wear resistance of the fabric. In addition, the wear-resistant particles distributed on the surface of the nanofibers have good wear resistance, which can further strengthen the fiber surface and significantly enhance its resistance to external wear forces. BRIEF DESCRIPTION OF THE DRAWINGS

[0051] Figure 1 This is a schematic diagram of the working process of the nano spinning machine of the present invention;

[0052] Figure 2 This is a SEM image of the wear-resistant nanofiber reinforced protective graphene fiber nanofiber membrane prepared in Example 1 of the present invention;

[0053] Figure 3 This is a schematic diagram of the wear-resistant nanofiber reinforced protective graphene fiber prepared in Example 1 of the present invention;

[0054] In the figure, 1-filament outlet shaft, 2-graphene fiber bundle after surface pretreatment, 3-motor I, 4-conical yarn guide, 5-spinneret, 6-graphene fiber bundle wrapped with nanofiber membrane, 7-guide hole, 8-filament collection shaft, 9-motor II. DETAILED DESCRIPTION

[0055] The present invention will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. In addition, it should be understood that after reading the content taught by the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms fall within the scope limited by the appended claims of the application equally.

[0056] In order to ensure that the properties of the materials used in each embodiment and comparative example are fully disclosed, the manufacturers and brands of the materials are indicated, and products of other manufacturers and brands that meet the requirements of the present invention are also feasible.

[0057] The testing methods of the relevant performance indicators in the following embodiments and comparative examples are as follows:

[0058] Tensile strength, tensile elastic modulus and toughness of the fiber: The wear-resistant nanofiber reinforced protective graphene fiber prepared in each embodiment is used as a sample, and then the tensile strength of the sample is tested according to GB / T 3362-2017 "Test method for tensile properties of carbon fiber multifilament" standard , tensile elastic modulus E and elongation at break (the adhesive used in the test is prepared in A.3.3 of the standard), and then the toughness is obtained by the calculation formula based on the integral stress-strain curve (the area under the stress-strain curve) obtained during the test. The calculation formula for toughness is: U= , where For strain, For stress.

[0059] Conductivity of fiber: The wear-resistant nanofiber reinforced protective graphene fiber prepared in each embodiment is used as a sample, and then the sample is laid flat on an insulating PET film, and the two ends are fixed with conductive double-sided tape to ensure that the contact section between the sample and the four-probe is straight and without bending. In the fiber test mode of the four-probe conductivity tester, the probe is pressed down to the surface of the sample, and then a current of 10 μA is applied through the four-probe conductivity tester. The voltage value V and the resistance value R=V / I are read, and then the conductivity of the sample is calculated based on the measured data. The calculation formula is: conductivity= , where l is the probe spacing (1.59 mm) and d is the diameter of the sample.

[0060] Thermal conductivity of fiber: The wear-resistant nanofiber reinforced protective graphene fiber prepared in each embodiment was used as a sample, and then the thermal conductivity of the sample was tested with reference to the Q / 110000 BH 008-2018 standard.

[0061] Specific wear rate of fiber: The wear-resistant nanofiber reinforced protective graphene fiber prepared in each embodiment is used as a sample, and then the wear resistance of the sample is tested on a reciprocating wear tester. Then, the weight loss of the sample after the test is obtained by comparing the weight of the sample before and after the test (in grams (g)), and then the specific wear rate (in mm) is calculated based on the measured data. 3 / (N·m)) to evaluate the wear resistance of the sample. The calculation formula of its specific wear rate is: specific wear rate = (ΔW×1000) / (ρ×L×F), where L is the total sliding distance during the wear process (in meters (m)), F is the normal force applied to the sample (in Newton (N)), and ρ is the density of the sample; Among them, the conditions for testing wear resistance are: the friction pair is Al 2 O 3Ceramic disk (Ra=0.8μm, diameter 30mm), reciprocating frequency 5Hz, stroke 10mm, test temperature 23℃, humidity 50%, total sliding distance during wear 500m, normal force applied to the sample 1.0N; the density of the sample was measured according to method C in GB / T30019-2013 standard, unit is g / cm 3 .

[0062] Bending strength, bending modulus and bending curvature of the fiber: The wear-resistant nanofiber reinforced protective graphene fiber prepared in each embodiment is used as a sample, and then a 500 mm sample is first wound on a multifilament frame according to the GB / T 3362-2017 standard, immersed in a 25°C resin glue (prepared according to A.3.3 in the GB / T 3362-2017 standard) and allowed to stand for 5 minutes, and then placed in a 120°C electric blast drying oven. After curing, a carbon fiber composite material specimen is obtained, and then the bending strength and bending modulus of the carbon fiber composite material specimen are tested according to the GB / T 1449-2005 "Fiber Reinforced Plastic Bending Performance Test Method" standard. In the three-point bending test, a laser displacement sensor (Keyence LK-G5000, accuracy ±0.5 μm) is used to synchronously record the load-displacement curve to obtain the maximum displacement δ (in mm) at the peak point of the curve, and then the curvature radius r ( , where is the span of the spline), and then the curvature is obtained according to the calculation formula , its curvature The calculation formula is: .

[0063] Tensile strength of fabric: The graphene fiber fabrics prepared in each embodiment and the control sample were used as samples, and then the samples were tested according to ASTM D5035-11 (2024) "Breaking Strength and Elongation of Textile Fabrics (Strip Method)" standard to obtain the maximum breaking strength (N), and then the tensile strength (MPa) was calculated based on the obtained data. The calculation formula is: Tensile strength = maximum breaking strength (N) / (effective width of sample × fabric thickness), where the effective width refers to the clamping width and the unit of fabric thickness is mm 2 .

[0064] Conductivity of fabric: The graphene fiber fabrics prepared in each embodiment and the comparative sample were cut into 20 mm × 20 mm sizes, and then the cut fabrics were used as samples for testing. The specific process was as follows: first, the sample was laid flat on the test bench, and the edge was fixed with a transparent pressing plate (to prevent wrinkling). Then, in the fabric test mode of the four-probe conductivity tester, the probe contacted the surface of the sample with a pressure of 50 mN, and then a current of 10 mA was applied through the four-probe conductivity tester to obtain the surface resistance. (unit: Ω / sq), and then calculate the conductivity of the sample (unit: S / m) based on the measured data. The calculation formula is: Conductivity = , where t is the thickness of the sample.

[0065] Thermal conductivity of fabric: The graphene fiber fabrics prepared in each embodiment and the control sample were used as samples, and then the samples were tested according to the standard GB / T 8722-2019 "Determination of thermal conductivity of carbon materials". Based on the flash method, the thermal diffusion coefficient α (in m 2 / s), and then the specific heat capacity c of the sample was measured by DSC p (unit: J / (kg·K)), the density of the sample is measured using GB / T 4668-1995 "Determination of density of woven fabrics", and then the thermal conductivity λ (unit: W / (m·K)) is calculated using the formula based on the measured data. The calculation formula is: , where ρ is the density.

[0066] Wear life: The graphene fiber fabrics prepared in each embodiment and the control sample were respectively used as samples, and then the samples were tested with reference to ISO 12947-2:2016 "Textiles—Determination of the abrasion resistance offabrics by the Martindale method". Alumina film (Ra≤0.1 μm) abrasive was selected on the Martindale tester. Under the stress condition of 9 kPa, Lissajous track friction was used to simulate multi-directional friction. The test was stopped when the single filament breakage was ≥10% (microscope random 5 area statistics), and the wear life was the number of friction cycles at the termination.

[0067] Bending fatigue life: The graphene fiber fabrics prepared in each embodiment and the comparative samples were cut into standard sizes of 25 mm × 50 mm as samples and tested using a dynamic mechanical analyzer. The specific process is as follows: a three-point bending mode is used, and the sample is first placed horizontally between two fixed support points (span L=40 mm), and then the maximum allowable bending angle of the sample is determined by preliminary experiments, and the cyclic bending angle is determined to be 10°, and then the three-point bending stress is calculated, and then the displacement control mode is selected, and a vertical downward cyclic load is applied at the center of the two fixed support points by a movable loading head (that is, the loading head moves up and down in the form of a sine wave with a frequency of 1 Hz), and when the test is started, the load-displacement curve is monitored in real time until the load drops to the sample fracture, and the number of cycles from the initial loading to the complete fracture of the sample is recorded at the same time, which is the bending fatigue life; Among them, the maximum allowable bending angle is determined as follows: the sample is quasi-statically bent to fracture, and δmax is obtained, and δcyclic=0.5×δmax is set, which is converted to a bending angle θ=10°; the calculation formula of the three-point bending stress is: three-point bending stress=3 FL / 2 bh 2 , where F is the loading load (N), the test software gives it in real time, L is the span, b is the sample width (i.e. 25 mm), h is the thickness of the sample (in μm).

[0068] Example 1

[0069] The preparation method of wear-resistant nanofiber reinforced protective graphene fiber comprises the following steps:

[0070] (1) Preparation of raw materials;

[0071] Wear-resistant particles: silicon dioxide, particle size 50~80nm;

[0072] Polymer material: polyurethane, manufactured by Covestro Polymers (China) Co., Ltd., brand name Desmocomp®385 S;

[0073] Graphene fiber tow: firstly, a GO (graphene oxide, lateral size of 10-50 μm, thickness of 1-5 nm) / DMF (N,N-dimethylformamide) solution with a concentration of 10 mg / g is wet-spun (coagulation bath is ethyl acetate) to obtain a graphene oxide fiber tow, then immersed in a hydroiodic acid / ethanol solution (volume ratio of hydroiodic acid to ethanol is 1:3) at 60°C for chemical reduction to obtain a chemically reduced graphene fiber tow, and then hot-stretched at 1200°C to obtain a graphene fiber tow;

[0074] The number of graphene fiber monofilaments in the prepared graphene fiber bundle is 20, the diameter of the graphene fiber bundle is 0.12 mm, the tensile strength is 950 MPa, the tensile elastic modulus is 100 GPa, and the toughness is 30 MJ / m 3, electrical conductivity is 1500S / cm, thermal conductivity is 300W / m·K, bending strength is 800MPa, bending modulus is 800MPa, bending curvature is 2%, and specific wear rate is 0.08mm 3 / (N·m);

[0075] Ethanol: purity is 99%;

[0076] Solvent in the polymer material solution: N,N-dimethylformamide and tetrahydrofuran in a volume ratio of 3:1;

[0077] (2) preparing spinning solution;

[0078] First, the polymer material is added to the solvent and the polymer material is completely dissolved, and then a magnetic stirrer is used to stir for 6 hours at 60° C. until the solution is completely uniform to obtain a polymer material solution with a concentration of 1wt%, and then the wear-resistant particles are added to the polymer material solution and ultrasonically treated with a power of 200W for 1 hour and then continued to stir until the wear-resistant particles are uniformly dispersed in the polymer material solution, and finally the polymer material solution is filtered using a filter membrane with a pore size of 0.45μm to obtain a spinning solution; wherein the mass ratio of the wear-resistant particles to the polymer material is 1:10;

[0079] (3) First, the graphene fiber bundle was immersed in ethanol for 10 minutes, then taken out and dried at 40°C for 6 hours, and then the dried graphene fiber bundle was subjected to plasma irradiation treatment in an oxygen atmosphere; wherein the pressure in the reaction chamber was 10Pa, the oxygen flow rate was 20sccm, the irradiation power was 50W, and the treatment time was 30s;

[0080] (4) If Figure 1 As shown, the graphene fiber bundle 2 after surface pretreatment is placed on the outlet shaft 1, and after the conical guide 4 and the collection shaft 8 are started by the motor I 3 and the motor II 9, the graphene fiber bundle 2 after surface pretreatment passes through the conical guide 4, and then the spinning solution prepared in step (2) is ejected through the spinneret 5 by electrospinning to form a nanofiber membrane and uniformly wrap the graphene fiber bundle 2 after surface pretreatment, so as to obtain a graphene fiber bundle 6 wrapped with a nanofiber membrane, which is then rolled into a shaft by the collection shaft 8 after passing through the guide hole 7; wherein the average diameter of the fibers in the nanofiber membrane is 50 nm, and the thickness of the nanofiber membrane is 10 μm;

[0081] The spinning process parameters were: voltage 15 kV, distance between needle and collector 5 cm, propulsion pump rate 0.5 mL / h, fiber reel take-up rate 0.1 cm / min, drying temperature 50 °C, spinning time 0.5 h;

[0082] (5) subjecting the fiber bundle wound in step (4) to a hot pressing roller treatment to obtain wear-resistant nanofiber reinforced protective graphene fiber;

[0083] The process parameters of the hot pressing roller treatment are: roller temperature 160°C, roller pressure 5MPa, roller speed 0.5m / min, and roller gap 80μm.

[0084] The wear-resistant nanofiber reinforced protective graphene fiber (the electron microscope image of the nanofiber membrane is as follows Figure 2 As shown in Figure 2), it is composed of graphene fiber bundles and nanofibers, such as Figure 3 As shown, the nanofibers are coated with graphene fiber bundles in the form of a three-dimensional porous network to form a stress buffer layer with a thickness of 3 μm; the wear-resistant particles are uniformly loaded inside the three-dimensional porous network;

[0085] Compared with untreated graphene fiber tows, the wear-resistant nanofiber reinforced protective graphene fibers have a 40% increase in tensile strength, a 40% increase in tensile elastic modulus, a 35% increase in toughness, an 8% increase in electrical conductivity, a 10% increase in thermal conductivity, a 40% increase in bending strength, a 45% increase in bending modulus, a 12% increase in bending curvature, and a 60% decrease in specific wear rate.

[0086] The application of wear-resistant nanofiber reinforced protective graphene fiber, the specific process is: the wear-resistant nanofiber reinforced protective graphene fiber prepared above is knitted to obtain graphene fiber fabric; wherein the number of needles (i.e., needle density) in the knitting process is 8 needles / inch;

[0087] The thickness of the graphene fiber fabric is 0.29 mm and the wear life is 8×10 3 times, the tensile strength is 360MPa, and the bending fatigue life is 3×10 3 times, the electrical conductivity is 250S / cm, and the thermal conductivity is 90W / (m·K);

[0088] The wear-resistant nanofiber reinforced protective graphene fiber is replaced by the graphene fiber bundle in the above step (1), and a control sample is prepared according to the same process as the graphene fiber fabric. Compared with the control sample, the wear resistance life of the graphene fiber fabric is increased by 150%, the tensile strength is increased by 30%, the bending fatigue life is increased by 80%, the electrical conductivity is increased by 8%, and the thermal conductivity is increased by 10%.

[0089] Example 2

[0090] The preparation method of wear-resistant nanofiber reinforced protective graphene fiber comprises the following steps:

[0091] (1) Preparation of raw materials;

[0092] Wear-resistant particles: aluminum oxide, particle size 150~200nm;

[0093] Polymer material: Polyetherimide, manufactured by Suzhou Jutai New Materials Co., Ltd., brand name JTYPEI ® NA;

[0094] Graphene fiber tow: firstly, a GO (graphene oxide, lateral size of 10-50 μm, thickness of 1-5 nm) / DMF solution with a concentration of 10 mg / g is wet-spun (coagulation bath is ethyl acetate) to obtain a graphene oxide fiber tow, then immersed in a hydroiodic acid / ethanol solution (volume ratio of hydroiodic acid to ethanol is 1:3) at 60°C for chemical reduction to obtain a chemically reduced graphene fiber tow, and then hot-stretched at 1200°C to obtain a graphene fiber tow;

[0095] The number of graphene fiber monofilaments in the prepared graphene fiber bundle is 50, the diameter of the graphene fiber bundle is 0.38 mm, the tensile strength is 850 MPa, the tensile elastic modulus is 90 GPa, and the toughness is 25 MJ / m 3 , electrical conductivity is 1200S / cm, thermal conductivity is 250W / m·K, bending strength is 700MPa, bending modulus is 70GPa, bending curvature is 1.80%, and specific wear rate is 0.1mm 3 / (N·m);

[0096] Ethanol: purity is 99%;

[0097] Solvent in the polymer material solution: N-methylpyrrolidone and dimethylsulfamide in a volume ratio of 1:1;

[0098] (2) preparing spinning solution;

[0099] First, the polymer material is added into the solvent and the polymer material is completely dissolved, and then a magnetic stirrer is used to stir for 4 hours at 90°C until the solution is completely uniform to obtain a polymer material solution with a concentration of 3wt%, and then the wear-resistant particles are added into the polymer material solution and ultrasonicated for 1 hour at a power of 300W and then stirred until the wear-resistant particles are uniformly dispersed in the polymer material solution, and finally the polymer material solution is filtered using a filter membrane with a pore size of 0.22μm to obtain a spinning solution; wherein the mass ratio of the wear-resistant particles to the polymer material is 1:15;

[0100] (3) First, the graphene fiber bundle was immersed in ethanol for 20 minutes, then taken out and dried at 45°C for 8 hours, and then the dried graphene fiber bundle was subjected to plasma irradiation treatment in an oxygen atmosphere; wherein the pressure in the reaction chamber was 60Pa, the oxygen flow rate was 40sccm, the irradiation power was 120W, and the treatment time was 190s;

[0101] (4) fixing the surface pretreated graphene fiber bundle on an electrospinning nano yarn machine, and then using the spinning solution prepared in step (2) to form a nanofiber membrane by electrospinning and uniformly wrapping the surface pretreated graphene fiber bundle, and then rolling it into a shaft; wherein the average fiber diameter in the nanofiber membrane is 150nm, and the thickness of the nanofiber membrane is 15μm;

[0102] The spinning process parameters were: voltage 25 kV, distance between needle and collector 7 cm, propulsion pump rate 1.5 mL / h, fiber reel take-up rate 1 cm / min, drying temperature 55 °C, spinning time 1 h;

[0103] (5) subjecting the fiber bundle wound in step (4) to a hot pressing roller treatment to obtain wear-resistant nanofiber reinforced protective graphene fiber;

[0104] The process parameters of the hot pressing roller treatment are: roller temperature 230°C, roller pressure 13MPa, roller speed 1.2m / min, and roller gap 105μm.

[0105] The wear-resistant nanofiber reinforced protective graphene fiber finally prepared is composed of graphene fiber bundles and nanofibers. The nanofibers cover the graphene fiber bundles in the form of a three-dimensional porous network to form a stress buffer layer with a thickness of 7 μm. The wear-resistant particles are evenly loaded inside the three-dimensional porous network.

[0106] Compared with untreated graphene fiber tows, the wear-resistant nanofiber reinforced protective graphene fibers have a 50% increase in tensile strength, a 45% increase in tensile elastic modulus, a 25% increase in toughness, a 15% increase in electrical conductivity, a 15% increase in thermal conductivity, a 45% increase in bending strength, a 50% increase in bending modulus, a 15% increase in bending curvature, and a 65% decrease in specific wear rate.

[0107] The application of wear-resistant nanofiber reinforced protective graphene fiber, the specific process is: the wear-resistant nanofiber reinforced protective graphene fiber prepared above is knitted to obtain graphene fiber fabric; wherein the number of needles in the knitting process is 15 needles / inch;

[0108] The thickness of the graphene fiber fabric is 0.91 mm, the wear life is 2 × 104 times, the tensile strength is 580 MPa, and the bending fatigue life is 8 × 10 3 times, the electrical conductivity is 350S / cm, and the thermal conductivity is 130W / (m·K);

[0109] The wear-resistant nanofiber reinforced protective graphene fiber was replaced by the graphene fiber tow in the above step (1), and a control sample was prepared according to the same process as the graphene fiber fabric. Compared with the control sample, the wear resistance life of the graphene fiber fabric was increased by 180%, the tensile strength was increased by 45%, the bending fatigue life was increased by 140%, the electrical conductivity was increased by 15%, and the thermal conductivity was increased by 12%.

[0110] Example 3

[0111] The preparation method of wear-resistant nanofiber reinforced protective graphene fiber comprises the following steps:

[0112] (1) Preparation of raw materials;

[0113] Wear-resistant particles: zirconium oxide, particle size 80~100nm;

[0114] Polymer material: poly(m-phenylene isophthalamide), the manufacturer is Chaomei New Materials Co., Ltd., the brand is X-FIPER Chaomei aramid fiber;

[0115] Graphene fiber tow: firstly, a GO (graphene oxide, lateral size of 10-50 μm, thickness of 1-5 nm) / DMF solution with a concentration of 10 mg / g is wet-spun (coagulation bath is ethyl acetate) to obtain a graphene oxide fiber tow, then immersed in a hydroiodic acid / ethanol solution (volume ratio of hydroiodic acid to ethanol is 1:3) at 60°C for chemical reduction to obtain a chemically reduced graphene fiber tow, and then hot-stretched at 1200°C to obtain a graphene fiber tow;

[0116] The number of graphene fiber monofilaments in the prepared graphene fiber bundle is 100, the diameter of the graphene fiber bundle is 0.45 mm, the tensile strength is 800 MPa, the tensile elastic modulus is 80 GPa, and the toughness is 20 MJ / m 3 , electrical conductivity is 1000S / cm, thermal conductivity is 200W / m·K, bending strength is 600MPa, bending modulus is 60GPa, bending curvature is 1.50%, and specific wear rate is 0.12mm 3 / (N·m);

[0117] Ethanol: purity is 99%;

[0118] Solvent in the polymer material solution: N-methylpyrrolidone and dimethylsulfamide in a volume ratio of 1:1;

[0119] (2) preparing spinning solution;

[0120] First, the polymer material is added into the solvent and the polymer material is completely dissolved, and then a magnetic stirrer is used to stir for 5 hours at 105°C until the solution is completely uniform to obtain a polymer material solution with a concentration of 5wt%, and then the wear-resistant particles are added into the polymer material solution and ultrasonicated at a power of 350W for 0.5h and then stirred until the wear-resistant particles are uniformly dispersed in the polymer material solution, and finally the polymer material solution is filtered using a PTFE filter membrane with a pore size of 0.45μm to obtain a spinning solution; wherein the mass ratio of the wear-resistant particles to the polymer material is 1:20;

[0121] (3) The graphene fiber bundle was first soaked and cleaned in ethanol for 30 minutes, then taken out and dried at 50°C for 10 hours, and then the dried graphene fiber bundle was subjected to plasma irradiation treatment in an oxygen atmosphere; wherein the pressure in the reaction chamber was 100 Pa, the oxygen flow rate was 100 sccm, the irradiation power was 200 W, and the treatment time was 300 s;

[0122] (4) fixing the surface pretreated graphene fiber bundle on an electrospinning nano yarn machine, and then using the spinning solution prepared in step (2) to form a nanofiber membrane by electrospinning and uniformly wrapping the surface pretreated graphene fiber bundle, and then rolling it into a shaft; wherein the average fiber diameter in the nanofiber membrane is 250nm, and the thickness of the nanofiber membrane is 40μm;

[0123] The spinning process parameters were: voltage 39 kV, distance between needle and collector 8 cm, propulsion pump rate 2 mL / h, fiber reel take-up rate 2 cm / min, drying temperature 60 °C, spinning time 2 h;

[0124] (5) subjecting the fiber bundle wound in step (4) to a hot pressing roller treatment to obtain wear-resistant nanofiber reinforced protective graphene fiber;

[0125] The process parameters of the hot pressing roller treatment are: roller temperature 400°C, roller pressure 20MPa, roller speed 2m / min, and roller gap 200μm.

[0126] The wear-resistant nanofiber reinforced protective graphene fiber finally prepared is composed of graphene fiber bundles and nanofibers. The nanofibers are coated with the graphene fiber bundles in the form of a three-dimensional porous network to form a stress buffer layer with a thickness of 20 μm. The wear-resistant particles are evenly loaded inside the three-dimensional porous network.

[0127] Compared with untreated graphene fiber tows, the wear-resistant nanofiber reinforced protective graphene fibers have a 50% increase in tensile strength, a 50% increase in tensile elastic modulus, a 25% increase in toughness, a 20% increase in electrical conductivity, a 20% increase in thermal conductivity, a 55% increase in bending strength, a 60% increase in bending modulus, a 20% increase in bending curvature, and a 70% decrease in specific wear rate.

[0128] The application of wear-resistant nanofiber reinforced protection graphene fiber, the specific process is: the wear-resistant nanofiber reinforced protection graphene fiber prepared above is weaved by a two-dimensional weaving method to obtain a graphene fiber fabric; wherein, the warp density is 20 strands / cm and the weft density is 35 strands / cm during the weaving process;

[0129] The thickness of the graphene fiber fabric is 1.08 mm, the wear life is 4×104 times, the tensile strength is 700 MPa, and the bending fatigue life is 2×10 4 times, the electrical conductivity is 1000S / cm, and the thermal conductivity is 200W / (m·K);

[0130] The wear-resistant nanofiber reinforced protective graphene fiber is replaced by the graphene fiber bundle in the above step (1), and a control sample is prepared according to the same process as the graphene fiber fabric. Compared with the control sample, the wear resistance life of the graphene fiber fabric is increased by 200%, the tensile strength is increased by 45%, the bending fatigue life is increased by 160%, the electrical conductivity is increased by 15%, and the thermal conductivity is increased by 20%.

[0131] Example 4

[0132] The preparation method of wear-resistant nanofiber reinforced protective graphene fiber comprises the following steps:

[0133] (1) Preparation of raw materials;

[0134] Wear-resistant particles: boron nitride nanotubes, with an average diameter of 20 nm and an average length of 1 μm;

[0135] Polymer material: poly(p-phenylene terephthalamide), manufactured by Taihe New Materials Group Co., Ltd., brand name Taipron® pulp;

[0136] Graphene fiber tow: firstly, a GO (graphene oxide, lateral size of 10-50 μm, thickness of 1-5 nm) / DMF solution with a concentration of 10 mg / g is wet-spun (coagulation bath is ethyl acetate) to obtain a graphene oxide fiber tow, then immersed in a hydroiodic acid / ethanol solution (volume ratio of hydroiodic acid to ethanol is 1:3) at 60°C for chemical reduction to obtain a chemically reduced graphene fiber tow, and then hot-stretched at 1200°C to obtain a graphene fiber tow;

[0137] The number of graphene fiber monofilaments in the prepared graphene fiber bundle is 500, the diameter of the graphene fiber bundle is 0.85 mm, the tensile strength is 700 MPa, the tensile elastic modulus is 70 GPa, and the toughness is 18 MJ / m 3, electrical conductivity is 800S / cm, thermal conductivity is 180W / m·K, bending strength is 500MPa, bending modulus is 50GPa, bending curvature is 1.20%, and specific wear rate is 0.15mm 3 / (N·m);

[0138] Ethanol: purity is 99%;

[0139] Solvent in the polymer material solution: N-methylpyrrolidone and dimethylsulfamide in a volume ratio of 1:1;

[0140] (2) preparing spinning solution;

[0141] First, the polymer material is added to the solvent and the polymer material is completely dissolved, and then a magnetic stirrer is used to stir for 6 hours at 120° C. until the solution is completely uniform to obtain a polymer material solution with a concentration of 8wt%, and then the wear-resistant particles are added to the polymer material solution and ultrasonicated at a power of 450W for 1 hour and then continued to stir until the wear-resistant particles are uniformly dispersed in the polymer material solution, and finally the polymer material solution is filtered using a PTFE filter membrane with a pore size of 1.0μm to obtain a spinning solution; wherein the mass ratio of the wear-resistant particles to the polymer material is 1:25;

[0142] (3) First, the graphene fiber bundle was immersed in ethanol for 10 minutes, then taken out and dried at 55°C for 12 hours, and then the dried graphene fiber bundle was subjected to plasma irradiation treatment in an oxygen atmosphere; wherein the pressure in the reaction chamber was 10Pa, the oxygen flow rate was 20sccm, the irradiation power was 50W, and the treatment time was 50s;

[0143] (4) fixing the surface pretreated graphene fiber bundle on an electrospinning nano yarn machine, and then using the spinning solution prepared in step (2) to form a nanofiber membrane by electrospinning and evenly wrapping the surface pretreated graphene fiber bundle, and then rolling it into a shaft; wherein the average fiber diameter in the nanofiber membrane is 225nm, and the thickness of the nanofiber membrane is 30μm;

[0144] The spinning process parameters were: voltage 15 kV, distance between needle and collector 5 cm, propulsion pump rate 0.5 mL / h, fiber reel take-up rate 0.5 cm / min, drying temperature 65 °C, spinning time 0.5 h;

[0145] (5) subjecting the fiber bundle wound in step (4) to a hot pressing roller treatment to obtain wear-resistant nanofiber reinforced protective graphene fiber;

[0146] The process parameters of the hot pressing roller treatment are: roller temperature 200°C, roller pressure 8MPa, roller speed 0.8m / min, and roller gap 100μm.

[0147] The wear-resistant nanofiber reinforced protective graphene fiber finally prepared is composed of graphene fiber bundles and nanofibers. The nanofibers are coated with the graphene fiber bundles in the form of a three-dimensional porous network to form a stress buffer layer with a thickness of 15 μm. The wear-resistant particles are evenly loaded inside the three-dimensional porous network.

[0148] Compared with untreated graphene fiber tows, the wear-resistant nanofiber reinforced protective graphene fibers have a 65% increase in tensile strength, a 60% increase in tensile elastic modulus, a 40% increase in toughness, an 18% increase in electrical conductivity, an 18% increase in thermal conductivity, a 65% increase in bending strength, a 75% increase in bending modulus, a 25% increase in bending curvature, and an 80% decrease in specific wear rate.

[0149] The application of wear-resistant nanofiber reinforced protection graphene fiber, the specific process is: the wear-resistant nanofiber reinforced protection graphene fiber prepared above is weaved by a two-dimensional weaving method to obtain a graphene fiber fabric; wherein, the warp density is 40 strands / cm and the weft density is 15 strands / cm during the weaving process;

[0150] The thickness of the graphene fiber fabric is 2.04 mm and the wear life is 3×10 4 times, the tensile strength is 650MPa, and the bending fatigue life is 1.5×10 4 times, the electrical conductivity is 800S / cm, and the thermal conductivity is 180W / (m·K);

[0151] The wear-resistant nanofiber reinforced protective graphene fiber was replaced by the graphene fiber bundle in the above step (1), and a control sample was prepared according to the same process as the graphene fiber fabric. Compared with the control sample, the wear resistance life of the graphene fiber fabric was increased by 220%, the tensile strength was increased by 50%, the bending fatigue life was increased by 180%, the electrical conductivity was increased by 12%, and the thermal conductivity was increased by 50%.

[0152] Example 5

[0153] The preparation method of wear-resistant nanofiber reinforced protective graphene fiber comprises the following steps:

[0154] (1) Preparation of raw materials;

[0155] Wear-resistant particles: graphene powder, with an average lateral size of 5 μm and an average thickness of 2 nm;

[0156] Polymer material: polybenzimidazole, the manufacturer is Dongguan Fulin Plastic Raw Materials Co., Ltd., the brand is Celazole PBI U60;

[0157] Graphene fiber tow: firstly, a GO (graphene oxide, lateral size of 10-50 μm, thickness of 1-5 nm) / DMF solution with a concentration of 10 mg / g is wet-spun (coagulation bath is ethyl acetate) to obtain a graphene oxide fiber tow, then immersed in a hydroiodic acid / ethanol solution (volume ratio of hydroiodic acid to ethanol is 1:3) at 60°C for chemical reduction to obtain a chemically reduced graphene fiber tow, and then hot-stretched at 1200°C to obtain a graphene fiber tow;

[0158] The number of graphene fiber monofilaments in the prepared graphene fiber bundle is 1000, the diameter of the graphene fiber bundle is 1.52 mm, the tensile strength is 600 MPa, the tensile elastic modulus is 60 GPa, and the toughness is 15 MJ / m 3 , electrical conductivity is 600S / cm, thermal conductivity is 150W / m·K, bending strength is 400MPa, bending modulus is 40GPa, bending curvature is 1%, and specific wear rate is 0.18mm 3 / (N·m);

[0159] Ethanol: purity is 99%;

[0160] Solvent in polymer material solution: N-methylpyrrolidone;

[0161] (2) preparing spinning solution;

[0162] First, the polymer material is added into the solvent and the polymer material is completely dissolved, and then a magnetic stirrer is used to stir for 2 hours at 160° C. until the solution is completely uniform to obtain a polymer material solution with a concentration of 10wt%, and then the wear-resistant particles are added into the polymer material solution and ultrasonically treated at a power of 550W for 45 minutes and then continued to stir until the wear-resistant particles are uniformly dispersed in the polymer material solution, and finally the polymer material solution is filtered using a filter membrane with a pore size of 0.45μm to obtain a spinning solution; wherein the mass ratio of the wear-resistant particles to the polymer material is 1:30;

[0163] (3) First, the graphene fiber bundle was immersed in ethanol for 20 minutes, then taken out and dried at 60°C for 6 hours, and then the dried graphene fiber bundle was subjected to plasma irradiation treatment in an oxygen atmosphere; wherein the pressure in the reaction chamber was 50 Pa, the oxygen flow rate was 40 sccm, the irradiation power was 80 W, and the treatment time was 100 s;

[0164] (4) fixing the surface pretreated graphene fiber bundle on an electrospinning nano yarn machine, and then using the spinning solution prepared in step (2) to form a nanofiber membrane by electrospinning and evenly wrapping the surface pretreated graphene fiber bundle, and then rolling it into a shaft; wherein the average fiber diameter in the nanofiber membrane is 400nm, and the thickness of the nanofiber membrane is 45μm;

[0165] The spinning process parameters were: voltage 20 kV, distance between needle and collector 6 cm, propulsion pump rate 1 mL / h, fiber reel take-up rate 1.5 cm / min, drying temperature 70 °C, spinning time 1 h;

[0166] (5) subjecting the fiber bundle wound in step (4) to a hot pressing roller treatment to obtain wear-resistant nanofiber reinforced protective graphene fiber;

[0167] The process parameters of the hot pressing roller treatment are: roller temperature 230°C, roller pressure 10MPa, roller speed 1m / min, and roller gap 110μm.

[0168] The wear-resistant nanofiber reinforced protective graphene fiber finally prepared is composed of graphene fiber bundles and nanofibers. The nanofibers are coated with the graphene fiber bundles in the form of a three-dimensional porous network to form a stress buffer layer with a thickness of 25 μm. The wear-resistant particles are evenly loaded inside the three-dimensional porous network.

[0169] Compared with untreated graphene fiber tows, the wear-resistant nanofiber reinforced protective graphene fibers have a 35% increase in tensile strength, a 30% increase in tensile elastic modulus, a 15% increase in toughness, a 25% increase in electrical conductivity, a 25% increase in thermal conductivity, a 35% increase in bending strength, a 40% increase in bending modulus, a 10% increase in bending curvature, and a 50% decrease in specific wear rate.

[0170] The application of wear-resistant nanofiber reinforced protection graphene fiber, the specific process is: the wear-resistant nanofiber reinforced protection graphene fiber prepared above is weaved by a two-dimensional weaving method to obtain a graphene fiber fabric; wherein, the warp density is 30 strands / cm and the weft density is 25 strands / cm during the weaving process;

[0171] The thickness of the graphene fiber fabric is 3.65 mm, the wear life is 5×104 times, the tensile strength is 750 MPa, and the bending fatigue life is 3×10 4 times, the electrical conductivity is 900S / cm, and the thermal conductivity is 190W / (m·K);

[0172] The wear-resistant nanofiber reinforced protective graphene fiber is replaced by the graphene fiber tow in the above step (1), and a control sample is prepared according to the same process as the graphene fiber fabric. Compared with the control sample, the wear resistance life of the graphene fiber fabric is increased by 180%, the tensile strength is increased by 30%, the bending fatigue life is increased by 120%, the electrical conductivity is increased by 20%, and the thermal conductivity is increased by 30%.

[0173] Example 6

[0174] The preparation method of wear-resistant nanofiber reinforced protective graphene fiber comprises the following steps:

[0175] (1) Preparation of raw materials;

[0176] Wear-resistant particles: titanium carbide MXene, with an average lateral size of 2 μm and an average thickness of 2 nm;

[0177] Polymer material: polyimide, manufactured by Jiangsu Aoshen New Materials Co., Ltd., brand name Fitlon®;

[0178] Graphene fiber tow: firstly, a GO (graphene oxide, lateral size of 10-50 μm, thickness of 1-5 nm) / DMF solution with a concentration of 10 mg / g is wet-spun (coagulation bath is ethyl acetate) to obtain a graphene oxide fiber tow, then immersed in a hydroiodic acid / ethanol solution (volume ratio of hydroiodic acid to ethanol is 1:3) at 60°C for chemical reduction to obtain a chemically reduced graphene fiber tow, and then hot-stretched at 1200°C to obtain a graphene fiber tow;

[0179] The number of graphene fiber monofilaments in the prepared graphene fiber bundle is 2000, the diameter of the graphene fiber bundle is 2.10 mm, the tensile strength is 500 MPa, the tensile elastic modulus is 50 GPa, and the toughness is 12 MJ / m 3 , electrical conductivity is 400S / cm, thermal conductivity is 120W / m·K, bending strength is 300MPa, bending modulus is 35GPa, bending curvature is 0.80%, and specific wear rate is 0.2mm 3 / (N·m);

[0180] Ethanol: purity is 99%;

[0181] Solvent in the polymer material solution: dimethylacetamide and N-methylpyrrolidone in a volume ratio of 1:1;

[0182] (2) preparing spinning solution;

[0183] First, the polymer material is added into the solvent and the polymer material is completely dissolved, and then a magnetic stirrer is used to stir for 4 hours at 85°C until the solution is completely uniform to obtain a polymer material solution with a concentration of 15wt%, and then the wear-resistant particles are added into the polymer material solution and ultrasonicated for 1 hour at a power of 600W and then stirred until the wear-resistant particles are uniformly dispersed in the polymer material solution, and finally the polymer material solution is filtered using a filter membrane with a pore size of 0.45μm to obtain a spinning solution; wherein the mass ratio of the wear-resistant particles to the polymer material is 1:35;

[0184] (3) The graphene fiber bundle was first soaked and cleaned in ethanol for 30 minutes, then taken out and dried at 40°C for 8 hours, and then the dried graphene fiber bundle was subjected to plasma irradiation treatment in an oxygen atmosphere; wherein the pressure in the reaction chamber was 60 Pa, the oxygen flow rate was 100 sccm, the irradiation power was 100 W, and the treatment time was 150 s;

[0185] (4) fixing the surface pretreated graphene fiber bundle on an electrospinning nano yarn machine, and then using the spinning solution prepared in step (2) to form a nanofiber membrane by electrospinning and uniformly wrapping the surface pretreated graphene fiber bundle, and then rolling it into a shaft; wherein the average fiber diameter in the nanofiber membrane is 500nm, and the thickness of the nanofiber membrane is 65μm;

[0186] The spinning process parameters were: voltage 25 kV, distance between needle and collector 7 cm, propulsion pump rate 1.5 mL / h, fiber reel take-up rate 1.8 cm / min, drying temperature 75 °C, spinning time 1.5 h;

[0187] (5) subjecting the fiber bundle wound in step (4) to a hot pressing roller treatment to obtain wear-resistant nanofiber reinforced protective graphene fiber;

[0188] The process parameters of the hot pressing roller treatment are: roller temperature 250°C, roller pressure 12MPa, roller speed 1.2m / min, and roller gap 130μm.

[0189] The wear-resistant nanofiber reinforced protective graphene fiber finally prepared is composed of graphene fiber bundles and nanofibers. The nanofibers are coated with the graphene fiber bundles in the form of a three-dimensional porous network to form a stress buffer layer with a thickness of 35 μm. The wear-resistant particles are evenly loaded inside the three-dimensional porous network.

[0190] Compared with untreated graphene fiber tows, the wear-resistant nanofiber reinforced protective graphene fibers have a 40% increase in tensile strength, a 50% increase in tensile elastic modulus, a 30% increase in toughness, a 30% increase in electrical conductivity, a 30% increase in thermal conductivity, a 45% increase in bending strength, a 50% increase in bending modulus, a 10% increase in bending curvature, and a 60% decrease in specific wear rate.

[0191] The application of wear-resistant nanofiber reinforced protective graphene fiber, the specific process is: the wear-resistant nanofiber reinforced protective graphene fiber prepared above is weaved by a three-dimensional weaving method to obtain a graphene fiber fabric; wherein, during the weaving process, the wear-resistant nanofiber reinforced protective graphene fiber in the directions of 0°, +45°, -45°, and 90° accounts for 50%, 12.5%, 12.5%, and 25% in the graphene fiber fabric respectively;

[0192] The thickness of the graphene fiber fabric is 5.04 mm, the wear life is 2 × 105 times, the tensile strength is 820 MPa, and the bending fatigue life is 8 × 10 4 times, the electrical conductivity is 1400S / cm, and the thermal conductivity is 280W / (m·K);

[0193] The wear-resistant nanofiber reinforced protective graphene fiber was replaced by the graphene fiber tow in the above step (1), and a control sample was prepared according to the same process as the graphene fiber fabric. Compared with the control sample, the wear resistance life of the graphene fiber fabric was increased by 220%, the tensile strength was increased by 50%, the bending fatigue life was increased by 180%, the electrical conductivity was increased by 18%, and the thermal conductivity was increased by 35%.

[0194] Example 7

[0195] The preparation method of wear-resistant nanofiber reinforced protective graphene fiber comprises the following steps:

[0196] (1) Preparation of raw materials;

[0197] Wear-resistant particles: composed of silicon dioxide and aluminum oxide in a mass ratio of 1:1, with a silicon dioxide particle size of 50~80nm and an aluminum oxide particle size of 150~200nm;

[0198] Polymer material: poly(p-phenylene benzobisoxazole), manufacturer: Chengdu Xinchen New Materials Technology Co., Ltd., brand: Hou Delun ® PBO pulp;

[0199] Graphene fiber tow: firstly, a GO (graphene oxide, lateral size of 10-50 μm, thickness of 1-5 nm) / DMF solution with a concentration of 10 mg / g is wet-spun (coagulation bath is ethyl acetate) to obtain a graphene oxide fiber tow, then immersed in a hydroiodic acid / ethanol solution (volume ratio of hydroiodic acid to ethanol is 1:3) at 60°C for chemical reduction to obtain a chemically reduced graphene fiber tow, and then hot-stretched at 1200°C to obtain a graphene fiber tow;

[0200] The number of graphene fiber monofilaments in the prepared graphene fiber bundle is 3000, the diameter of the graphene fiber bundle is 2.54 mm, the tensile strength is 400 MPa, the tensile elastic modulus is 40 GPa, and the toughness is 10 MJ / m 3 , electrical conductivity is 300S / cm, thermal conductivity is 100W / m·K, bending strength is 250MPa, bending modulus is 30GPa, bending curvature is 0.70%, and specific wear rate is 0.25mm 3 / (N·m);

[0201] Ethanol: purity is 99%;

[0202] Solvent in the polymer material solution: N-methylpyrrolidone and dimethylsulfamide in a volume ratio of 1:2;

[0203] (2) preparing spinning solution;

[0204] First, the polymer material is added to the solvent and the polymer material is completely dissolved, and then a magnetic stirrer is used to stir for 6 hours at 75°C until the solution is completely uniform to obtain a polymer material solution with a concentration of 18wt%, and then the wear-resistant particles are added to the polymer material solution and ultrasonically treated for 1 hour at a power of 450W and then continued to stir until the wear-resistant particles are uniformly dispersed in the polymer material solution, and finally the polymer material solution is filtered using a filter membrane with a pore size of 0.45μm to obtain a spinning solution; wherein the mass ratio of the wear-resistant particles to the polymer material is 1:40;

[0205] (3) The graphene fiber bundle was first soaked and cleaned in ethanol for 20 minutes, then taken out and dried at 50°C for 10 hours, and then the dried graphene fiber bundle was subjected to plasma irradiation treatment in an oxygen atmosphere; wherein the pressure in the reaction chamber was 80 Pa, the oxygen flow rate was 60 sccm, the irradiation power was 150 W, and the treatment time was 200 s;

[0206] (4) fixing the surface pretreated graphene fiber bundle on an electrospinning nano yarn machine, and then using the spinning solution prepared in step (2) to form a nanofiber membrane by electrospinning and evenly wrapping it on the surface pretreated graphene fiber bundle, and then rolling it into a shaft; wherein the average fiber diameter in the nanofiber membrane is 450nm, and the thickness of the nanofiber membrane is 100μm;

[0207] The spinning process parameters were: voltage 30 kV, distance between needle and collector 8 cm, propulsion pump rate 2 mL / h, fiber reel take-up rate 0.8 cm / min, drying temperature 80 °C, spinning time 2 h;

[0208] (5) subjecting the fiber bundle wound in step (4) to a hot pressing roller treatment to obtain wear-resistant nanofiber reinforced protective graphene fiber;

[0209] The process parameters of the hot pressing roller treatment are: roller temperature 300°C, roller pressure 15MPa, roller speed 1.4m / min, and roller gap 150μm.

[0210] The wear-resistant nanofiber reinforced protective graphene fiber finally prepared is composed of graphene fiber bundles and nanofibers. The nanofibers cover the graphene fiber bundles in the form of a three-dimensional porous network to form a stress buffer layer with a thickness of 60 μm. The wear-resistant particles are evenly loaded inside the three-dimensional porous network.

[0211] Compared with untreated graphene fiber tows, the wear-resistant nanofiber reinforced protective graphene fibers have a 45% increase in tensile strength, a 40% increase in tensile elastic modulus, a 15% increase in toughness, a 35% increase in electrical conductivity, a 35% increase in thermal conductivity, a 50% increase in bending strength, a 55% increase in bending modulus, a 10% increase in bending curvature, and a 70% decrease in specific wear rate.

[0212] The application of wear-resistant nanofiber reinforced protective graphene fiber, the specific process is: the wear-resistant nanofiber reinforced protective graphene fiber prepared above is weaved by a three-dimensional weaving method to obtain a graphene fiber fabric; wherein, during the weaving process, the wear-resistant nanofiber reinforced protective graphene fiber in the directions of 0°, +45°, -45°, and 90° accounts for 60%, 10%, 10%, and 20% of the graphene fiber fabric respectively;

[0213] The thickness of the graphene fiber fabric is 6.10 mm, the wear life is 1.5 × 105 times, the tensile strength is 750 MPa, and the bending fatigue life is 6 × 10 4 times, the electrical conductivity is 1300S / cm, and the thermal conductivity is 260W / (m·K);

[0214] The wear-resistant nanofiber reinforced protective graphene fiber was replaced by the graphene fiber bundle in the above step (1), and a control sample was prepared according to the same process as the graphene fiber fabric. Compared with the control sample, the wear resistance life of the graphene fiber fabric was increased by 240%, the tensile strength was increased by 55%, the bending fatigue life was increased by 160%, the electrical conductivity was increased by 10%, and the thermal conductivity was increased by 30%.

[0215] Example 8

[0216] The preparation method of wear-resistant nanofiber reinforced protective graphene fiber comprises the following steps:

[0217] (1) Preparation of raw materials;

[0218] Wear-resistant particles: aluminum oxide, particle size 250~300nm;

[0219] Polymer materials: 2,3,5,6-tetraaminopyridine hydrochloride and 2,5-dihydroxyterephthalic acid were added to polyphosphoric acid (manufacturer: Shanghai Aladdin Biochemical Technology Co., Ltd., product number: P102919) at a molar ratio of 1:1.02 to obtain a mixed solution with a solid content of 15wt%, and then the system was replaced with nitrogen, heated to 60°C and evacuated to -0.095MPa to remove HCl in 2,3,5,6-tetraaminopyridine hydrochloride (tested by pH paper until no HCl gas was precipitated), and then heated to 80°C at a heating rate of 1°C / min, and then continued to heat to 95°C at a rate of 0.5°C / min and kept warm for 24h to complete the polycondensation reaction to obtain PIPD polymer;

[0220] Then, the obtained PIPD polymer solution is spun by dry-jet wet spinning, and the spun fiber is immersed in distilled water until the pH of the system is 7 to remove polyphosphoric acid, and finally, it is placed in a 60°C blast drying oven to remove the residual water in the fiber, thereby obtaining poly 2,5-dihydroxy-1,4-phenylene pyridine diimidazole fiber; wherein the pore size of the spinneret is 25 μm, and the coagulation bath is distilled water at 30°C;

[0221] The average diameter of the obtained poly 2,5-dihydroxy-1,4-phenylene pyridinium diimidazole fiber is 50 μm, the thermal decomposition temperature is 530°C, and the tensile strength of the primary fiber is 1.2 GPa;

[0222] Graphene fiber tow: firstly, a GO (graphene oxide, lateral size of 10-50 μm, thickness of 1-5 nm) / DMF solution with a concentration of 10 mg / g is wet-spun (coagulation bath is ethyl acetate) to obtain a graphene oxide fiber tow, then immersed in a hydroiodic acid / ethanol solution (volume ratio of hydroiodic acid to ethanol is 1:3) at 60°C for chemical reduction to obtain a chemically reduced graphene fiber tow, and then hot-stretched at 1200°C to obtain a graphene fiber tow;

[0223] The number of graphene fiber monofilaments in the prepared graphene fiber bundle is 3000, the diameter of the graphene fiber bundle is 2.94 mm, the tensile strength is 350 MPa, the tensile elastic modulus is 35 GPa, and the toughness is 8 MJ / m 3 , electrical conductivity is 200S / cm, thermal conductivity is 80W / m·K, bending strength is 200MPa, bending modulus is 25GPa, bending curvature is 0.60%, and specific wear rate is 0.3mm 3 / (N·m);

[0224] Ethanol: purity is 99%;

[0225] Solvent in polymer material solution: methanesulfonic acid;

[0226] (2) preparing spinning solution;

[0227] First, the polymer material is added to the solvent and the polymer material is completely dissolved, and then a magnetic stirrer is used to stir for 6 hours at 50°C until the solution is completely uniform to obtain a polymer material solution with a concentration of 20wt%, and then the wear-resistant particles are added to the polymer material solution and ultrasonically treated with a power of 300W for 1 hour and then continued to stir until the wear-resistant particles are uniformly dispersed in the polymer material solution, and finally the polymer material solution is filtered with a filter membrane with a pore size of 0.22μm to obtain a spinning solution; wherein the mass ratio of the wear-resistant particles to the polymer material is 1:50;

[0228] (3) The graphene fiber bundle was first soaked and cleaned in ethanol for 30 minutes, then taken out and dried at 60°C for 12 hours, and then the dried graphene fiber bundle was subjected to plasma irradiation treatment in an oxygen atmosphere; wherein the pressure in the reaction chamber was 100 Pa, the oxygen flow rate was 100 sccm, the irradiation power was 200 W, and the treatment time was 250 s;

[0229] (4) fixing the graphene fiber bundle after surface pretreatment on an electrospinning nano yarn machine, and then using the spinning solution prepared in step (2) to form a nanofiber membrane by electrospinning and evenly wrapping it on the graphene fiber bundle after surface pretreatment, and then rolling it into a shaft; wherein the average fiber diameter in the nanofiber membrane is 800nm, and the thickness of the nanofiber membrane is 100μm;

[0230] The spinning process parameters were: voltage 35 kV, distance between needle and collector 5 cm, propulsion pump rate 0.5 mL / h, fiber reel take-up rate 0.2 cm / min, drying temperature 65 °C, spinning time 0.5 h;

[0231] (5) subjecting the fiber bundle wound in step (4) to a hot pressing roller treatment to obtain wear-resistant nanofiber reinforced protective graphene fiber;

[0232] The process parameters of the hot pressing roller treatment are: roller temperature 400°C, roller pressure 18 MPa, roller speed 1.8 m / min, and roller gap 180 μm.

[0233] The wear-resistant nanofiber reinforced protective graphene fiber finally prepared is composed of graphene fiber bundles and nanofibers. The nanofibers are coated with the graphene fiber bundles in the form of a three-dimensional porous network to form a stress buffer layer with a thickness of 70 μm. The wear-resistant particles are evenly loaded inside the three-dimensional porous network.

[0234] Compared with untreated graphene fiber tows, the wear-resistant nanofiber reinforced protective graphene fibers have a 30% increase in tensile strength, a 25% increase in tensile elastic modulus, a 10% increase in toughness, a 40% increase in electrical conductivity, a 50% increase in thermal conductivity, a 35% increase in bending strength, a 40% increase in bending modulus, a 10% increase in bending curvature, and a 60% decrease in specific wear rate.

[0235] The application of wear-resistant nanofiber reinforced protective graphene fiber, the specific process is: the wear-resistant nanofiber reinforced protective graphene fiber prepared above is weaved by a three-dimensional weaving method to obtain a graphene fiber fabric; wherein, during the weaving process, the wear-resistant nanofiber reinforced protective graphene fiber in the directions of 0°, +45°, -45°, and 90° accounts for 55%, 12.5%, 12.5%, and 20% in the graphene fiber fabric respectively;

[0236] The thickness of the graphene fiber fabric is 7.06 mm, the wear life is 2.5×104 times, the tensile strength is 880 MPa, and the bending fatigue life is 1×10 5 times, the electrical conductivity is 1500S / cm, and the thermal conductivity is 300W / (m·K);

[0237] The wear-resistant nanofiber reinforced protective graphene fiber was replaced by the graphene fiber tow in the above step (1), and a control sample was prepared according to the same process as the graphene fiber fabric. Compared with the control sample, the wear resistance life of the graphene fiber fabric was increased by 180%, the tensile strength was increased by 35%, the bending fatigue life was increased by 120%, the electrical conductivity was increased by 5%, and the thermal conductivity was increased by 20%.

Claims

1. A method for preparing wear-resistant nanofiber reinforced protective graphene fiber, characterized in that: The surface pretreated graphene fiber is fixed on an electrospinning nano yarn machine, a nanofiber membrane is formed by electrospinning and uniformly wrapped on the surface pretreated graphene fiber, and then rolled into a shaft, and then the rolled fiber bundle is subjected to a hot pressing roller treatment to obtain wear-resistant nanofiber reinforced protective graphene fiber; The surface pretreatment adopts the method of plasma irradiation treatment; The spinning solution used in electrospinning is obtained by adding wear-resistant particles to a polymer material solution; the wear-resistant particles are one or more of silica, alumina, zirconium oxide, boron nitride nanotubes, graphene powder and titanium carbide MXene, and the polymer material is polyurethane, polyetherimide, poly(m-phenylene isophthalamide), poly(p-phenylene terephthalamide), polybenzimidazole, polyimide, poly(p-phenylene benzobisoxazole) fiber or poly (2,5-dihydroxy-1,4-phenylene pyridine diimidazole).

2. The method for preparing wear-resistant nanofiber reinforced protective graphene fiber according to claim 1, characterized in that: The plasma irradiation treatment adopts an oxygen atmosphere, the pressure in the reaction chamber is 10~100Pa, the oxygen flow rate is 20~100sccm, the irradiation power is 50~200W, and the treatment time is 30~300s.

3. The method for preparing wear-resistant nanofiber reinforced protective graphene fiber according to claim 1, characterized in that: The mass ratio of the wear-resistant particles to the polymer material is 1:10-50, and the concentration of the polymer material solution is 1-20wt%.

4. The method for preparing wear-resistant nanofiber reinforced protective graphene fiber according to claim 1, characterized in that: The spinning process parameters are: voltage 15~39kV, distance between needle and collector 5~8cm, propulsion pump rate 0.5~2mL / h, fiber reel winding rate 0.1~2cm / min, drying temperature 50~80℃, spinning time 0.5~2h.

5. The method for preparing wear-resistant nanofiber reinforced protective graphene fiber according to claim 4, characterized in that: The average fiber diameter in the nanofiber membrane is 50~1000nm, and the thickness of the nanofiber membrane is 3~100μm.

6. The method for preparing wear-resistant nanofiber reinforced protective graphene fiber according to claim 1, characterized in that: The process parameters of hot pressing roller treatment are: roller temperature 160~400℃, roller pressure 5~20MPa, roller speed 0.5~2m / min, roller gap 80~200μm.

7. The wear-resistant nanofiber reinforced protective graphene fiber prepared by the preparation method according to any one of claims 1 to 6, characterized in that: It includes graphene fiber bundles and nanofibers. The nanofibers wrap the graphene fiber bundles in the form of a three-dimensional porous network to form a stress buffer layer; the wear-resistant particles are evenly loaded inside the three-dimensional porous network.

8. The use of wear-resistant nanofiber reinforced protective graphene fiber as claimed in claim 7, characterized in that: Used in weaving and preparing graphene fiber fabrics.

9. The use of wear-resistant nanofiber reinforced protective graphene fiber according to claim 8, characterized in that: The weaving method is knitting, two-dimensional weaving or three-dimensional weaving.

Citation Information

Patent Citations

  • A preparation method of graphene paper prepreg

    CN105254920B

  • Anodic oxidation method of high-strength medium-modulus polyacrylonitrile-based carbon fiber and carbon fiber

    CN118996562A

  • High-strength wear-resistant nanofiber composite yarn and preparation method thereof

    CN103014978A

  • Orientation electro-spinning nanometer fiber spinning method and device thereof

    CN103132194A

  • Ultraviolet-proof nano-fiber yarn and preparation method thereof

    CN105839253A

Cited By

  • Preparation method of basalt fiber-containing epoxy resin composite board for automobile

    CN121064603A

  • A method for preparing an epoxy resin composite plate for an automobile containing basalt fibers

    CN121064603B